2011
DOI: 10.1242/jeb.054643
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts from long-lived bird species are resistant to multiple forms of stress

Abstract: number of mouse-sized passerines (e.g. swallows and sparrows) can live as much as three to four times longer than mice. Birds achieve this remarkable longevity despite their exceptionally high metabolic rate coupled with the high energetic demands of .37, P<0.01). They did not differ in their resistance to UV radiation, or to thapsigargin or tunicamycin, inducers of the unfolded protein response. These results were largely consistent even after accounting for the influence of body mass and phylogeny. Cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 69 publications
(91 reference statements)
7
61
0
2
Order By: Relevance
“…In addition, fibroblasts from long-lived rodent and bird species require higher doses of a range of oxidants to cause lethality than do fibroblasts from shorter-lived species (2,3). Similar findings have been made by other studies using smaller sets of animals (4)(5)(6).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, fibroblasts from long-lived rodent and bird species require higher doses of a range of oxidants to cause lethality than do fibroblasts from shorter-lived species (2,3). Similar findings have been made by other studies using smaller sets of animals (4)(5)(6).…”
Section: Introductionsupporting
confidence: 83%
“…LD 50 assays. LD 50 experiments were performed using WST-1 reagent as described previously (2,3). Where specified in the figures, cells were cultured in media supplemented with 40 ng/ml of recombinant rat IFN-γ for 24 hours, prior to exposure to H 2 O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…To test this idea, Kapahi et al (Kapahi et al, 1999) examined the resistance of primary fibroblasts of eight species of mammals, ranging in body mass from 0.1 to 450kg, to chemicals that imposed oxidative and non-oxidative stress. Even with such a small sample size, they found that cells from large, long-lived mammals resisted chemical stress agents better than cells from small short-lived mammals, a finding later supported by results from skin-derived fibroblasts of both rodents (Harper et al, 2007) and birds (Harper et al, 2011). Furthermore, cells from renal epithelium isolated from long-lived birds have also been found to have higher resistance to oxidative stressors (Ogburn et al, 1998).…”
Section: Introductionmentioning
confidence: 92%
“…We established primary fibroblast cell cultures after the skin was exposed to 1.5% Collagenase B solution overnight (Harper et al, 2007). Cells were grown in culture flasks at 37°C in an atmosphere of 3% O 2 (Harper et al, 2011). When cells reached 90% confluence, they were trypsinized (0.25%) and passaged.…”
Section: Introductionmentioning
confidence: 99%
“…We controlled oxygen levels, because cells exposed to 21 % O 2 are susceptible to early growth crisis, increased levels of oxidative stress, and do not live as long in culture as compared with cells grown at reduced oxygen levels (Chakravarthy et al 2001;Parrinello et al 2003;Harper et al 2011). We standardized the number of cells per well to 15,000.…”
Section: Metabolic Rate Of Myoblastsmentioning
confidence: 99%